Behavior of Pacific Walruses (Odobenus rosmarus divergens) Hauled Out on Sea Ice During UAS Overflights, Eastern Chukchi Sea, 2015 ... - Brian C Battaile; Chadwick V Jay; Anthony S Fischbach (U.S. Geological Survey, 2022)
This dataset is comprised of three tables showing the reaction of walruses hauled out on sea ice of the Chukchi Sea to overflights by rotary wing Unoccupied Aircraft Systems (UAS). Data include behavior of walruses before, during, and after overflights, and environmental conditions during flights. ...